Study the Level of Customer Satisfaction at the Government’s One-Stop Service Center in Luang Prabang Capital - Bounchanpaseuth, Bouahieng; Inthapanya, Sangkhom; Silivanh, Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
general characteristics of service users at the government’s one-stop service center in Luang Prabang capital, and 2) to study the level of customer satisfaction at the government’s one-stop service center in Luang Prabang Capital. This study employed a survey research design. The target population consisted of 384 people at the government’s one-stop service center in Luang Prabang capital, Luang Prabang Province. Data were collected using a questionnaire, and the data were analyzed using SPSS version 26 to calculate percentages, mean values, and standard deviations. The results found that: The general characteristics of service users at the government one-stop service center in Luang Prabang Capital are predominantly male, aged between 36 and 41 years, belonging to the Lao Loum ethnic group, married, having an educational attainment below the bachelor’s degree level, employed as government officials, and earning an average monthly income of 1,000,000–5,000,000 kip. Most users primarily choose services related to birth registration, land registration, business registration, construction permits, and transportation services. Overall, the level of satisfaction of service users at the government one-stop service center in Luang Prabang capital is a moderate level, with a mean of 2.84 and a standard deviation (SD) of 0.27. This includes satisfaction with continuous service delivery, progressive service provision, prompt and timely service, adequate service provision, and equitable service delivery.